The Most Indispensable Habits of Effective Theological Educators: Recalibrating Educational Philosophy, Psychology, and Practice - Lamport, Mark A. (The Asbury journal, 2010)
In this article, the author provocatively claims that "theological education is neither"; it is not theological unless it is considers the nature of its mission to be ultimately Ministerial; and it is not education unless it takes seriously the learner as focal point of the process.